XRD-Based Structural and Crystallite Size Analysis of Nano-MgO Prepared via Sol–gel Method - Imas Masriah; Devi Lestari; Sulwiyatul Kamariyah Sani; Inten Pangestika; Dikki Miswanda (KOVALEN: Jurnal Riset Kimia, 2025)
Nano-MgO was synthesized via a nitrate–citrate sol–gel combustion method, in which magnesium nitrate acted as the oxidizing precursor and citric acid served simultaneously as the chelating agent and organic fuel. The formation of a homogeneous Mg–citrate coordination network enabled controlled gelation, while the auto-combustion process produced a porous MgO matrix composed of ultrafine crystallites. Calcination at 800 °C promoted phase consolidation, removal of organic residues, and enhanced long-range atomic ordering. X-ray diffraction confirmed the exclusive formation of the cubic periclase phase (fm3m), with no detectable hydroxide or carbonate impurities. Crystallite size analysis yielded an average size of 16.03 nm based on the Scherrer equation, whereas the Williamson–Hall method produced a larger value of 25.44 nm with a microstrain of 5.37 × 10-4. indicating minimal lattice distortion. The discrepancy between the two size estimates reflects the contribution of microstrain effect not considered in the Scherrer approach. Overall, the synthesized nano-MgO exhibits high crystallinity, narrow crystallite size distribution, and excellent structural stability, highlighting its potential for catalytic, gas-sensing, and high-temperature functional applications. These results demonstrate that the sol–gel combustion method is an efficient and reliable strategy for producing nanocrystalline MgO with well-controlled structural characteristics.